Loss of mTOR repressors Tsc1 or Pten has divergent effects on excitatory and inhibitory synaptic transmission in single hippocampal neuron cultures - Weston, Matthew C.; Chen, Hongmei; Swann, John W. (Frontiers in Molecular Neuroscience, 2014)
The Pten and Tsc1 genes both encode proteins that repress mechanistic target of rapamycin (mTOR) signaling. Disruption of either gene in the brain results in epilepsy and autism-like symptoms in humans and mouse models, therefore it is important to understand the molecular and physiological events that lead from gene disruption to disease phenotypes. Given the similar roles these two molecules play in the regulation of cellular growth and the overlap in the phenotypes that result from their loss, we predicted that the deletion of either the Pten or Tsc1 gene from hippocampal neurons would have similar effects on neuronal morphology and synaptic transmission. Accordingly, we found that loss of either Pten or Tsc1 caused comparable increases in soma size, dendrite length and action potential properties. However, the effects of Pten and Tsc1 loss on synaptic transmission were different. Loss of Pten lead to an increase in both excitatory and inhibitory neurotransmission, while loss of Tsc1 did not affect excitatory neurotransmission and reduced inhibitory transmission by decreasing mIPSC amplitude. Although the loss of Pten or Tsc1 both increased downstream mTORC1 signaling, phosphorylation of Akt was increased in Pten-ko and decreased in Tsc1-ko neurons, potentially accounting for the different effects on synaptic transmission. Despite the different effects at the synaptic level, our data suggest that loss of Pten or Tsc1 may both lead to an increase in the ratio of excitation to inhibition at the network level, an effect that has been proposed to underlie both epilepsy and autism.